Ecologia reprodutiva de Leptodactylus Furnarjus (Leptodactylidae), um anuro que desova em câmara subterrânea - Kokubum, Marcelo Nogueira de Carvalho (2001)
Kokubum, M. N. de C. 2001. Reproductive ecology of Leptodactylus furnarius (Leptodactylidae), a frog that lays eggs in underground chambers. MSc. Thesis. UFU. Uberlândia-MG. 22p. This paper describes the reproductive ecology of Leptodactylus furnarius (Anura, Leptodactylidae) in a Cerrado area, in Uberlândia municipality, Minas Gerais State, Brazil. The field observations and the samples were accomplished during two reproductive seasons, in the period from October 1999 to June 2001. The analysed individuais were collected through pitfall with drift fences. The fecundity of the females was determined during all study period with base in the ovarian complements. L. furnarius reproduced in the wet/hot season, that during about 7 months and it presented the behavior of construction of underground chambers for the deposition of the eggs, pattems of reproduction agrees with other species of Leptodactylus of the group fuscus. L. furnarius used swampy places (Veredas) to reproduce, in spite of being also found in humid sites in the urban area. The individuais' capture was low or null in months with inferior precipitation to 100 mm. The juvenile ones varied significantly in size along the months being found in most of these. Females prevailed in the samples, with high operational sexual ratio (egg-bearing females/males). There was sexual dimorphism being the females (CRC = 42,4 mm) larger than the males (CRC = 38,0 mm). The fecundity, estimated in the ovaries varied from 27 to 119 eggs and foam nests found in the field presented between 31 and 99 eggs. The vitelinic portion of the eggs was cream colored and and measured about 3 mm of diameter. The mating behavior was observed, where the male leads the female for an underground chamber previously excavated. The underground chamber presented a simple contruction with a direct entrance or a short tunnel and it was built in muddy soil, among grass roots. Tadpoles produced foam without parental help. A juvenile snake (Liophis meridionalis) was found preying tadpoles inside of the foam and an another snake, an adult individual of Thamnodynastes strigilis preying an egg-bearing-female. The probable difference of the sexual rate and of the operational sexual rate could be in function of ecological factors, as the largest dispersion of females between the call sites and reproduction places while males could, probably, just to stay around close areas on the underground chambers. The foam production by the tadpoles independent of the action of the parentals corroborates the hypothesis that this behavior represents a shared characteristic among the species of Leptodactylus of the fuscus group. The predation of eggs/tadpoles of species of L. fuscus group inside of the nest is few documented, so that the unpublished observation in this work, complement the list of potential predators of anuran adult and larval forms.